2017
DOI: 10.14814/phy2.13248
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate variability and exercise capacity in Type 1 diabetes

Abstract: People with type 1 diabetes (T1D) have lower exercise capacity (V̇O2max) than their age‐matched nondiabetic counterparts (CON), which might be related to cardiac autonomic dysfunction. We examined whether Heart Rate Variability (HRV; indicator of cardiac autonomic modulation) was associated with exercise capacity in those with and without T1D. Twenty‐three participants with uncomplicated T1D and 17 matched CON were recruited. Heart rate (HR; ECG), blood pressure (BP; finger photo‐plethysmography), and respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…Several studies found a decreased exercise performance in comparison of individuals with T1DM and their healthy counterparts [ 25 ][ 26 ]. However, little research exists on its relation to glycaemic control [ 13 ], and to the best of our knowledge, no trials investigated the influence of CI on exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found a decreased exercise performance in comparison of individuals with T1DM and their healthy counterparts [ 25 ][ 26 ]. However, little research exists on its relation to glycaemic control [ 13 ], and to the best of our knowledge, no trials investigated the influence of CI on exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are numerous strengths, it is important to consider certain limitations in the interpretation of this study. We acknowledge the controversy that surrounds interpretation of HF, LF and LF:HF [27], however, HRV is a non-invasive tool that provides prognostic insight into global cardiovascular health [47,57,60]. The small sample size limits our statistical power and a larger study is required to ratify our findings.…”
Section: Discussionmentioning
confidence: 86%
“…To determine the intensity of physical activities in both experiments, the heart rate (HR) was recorded every 2 min during the task. The basal HR 23 was measured in a supine position on a different day.…”
Section: Methodsmentioning
confidence: 99%